Byond Unions and Collective Bargaining - Taras, Daphne (Relations industrielles / Industrial Relations, 2002)
Beyond Unions and Collective Bargaining, by Leo Troy, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z